Efficiency of different selection indexes for desired gain by ’bending’ of parameter estimates - KHANNA, A S; JAISWAL, U C (The Indian Journal of Animal Sciences, 2013)
Data pertaining to 116 Holstein-Friesian X Hariana (F1) crossbred cows were utilized for evaluating the efficiency of different selection indexes for desired gains by ’bending’ of parameter estimates. Indexes with breeding objectives of direct improvement in traits included in the index were superior in general, than those involving indirect breeding goals. These differences were distinct when indexes were made from original parameter estimates (without bending). In general. bending of parameter estimates, improved the efficiency of all indexes at all values of bending factor; however, 0.7 to 0.9 was the best in the present case. When improvement in lifetime production and breeding efficiency was the goal. the index constructed using first lactation traits. i.e. age at first calving, first lactation yield and first calving interval required higher number of generations but was overall more efficient than the index incorporating lifetime traits, because of shorter generation interval (3.7 vs 6.0 years).